Narzędzie doboru zindywidualizowanych strategii utrzymania dyscypliny (ZSUD) w klasie szkolnej - Ewa Lemańska-Lewandowska (Problemy Wczesnej Edukacji)
This article presents a standardized research tool containing a number of strategies that can help discipline in the classroom drawn from various known models of discipline. Attention was paid to the opportunity for specialists such as educators, psychologists, therapists, and/or teachers to work with this tool. The tool helps to facilitate the recognition of undesirable behaviour in the classroom and facilitates the selection of a whole set of policies of discipline that is used to solve a particular problem and that can be applied to a particular student, his/her style of behaviour, and the level of motivation presented by him/her.